Peningkatan Hasil Belajar Ipa Siswa Kelas V Dengan Menggunakan Metode Inkuiri - Zaiyasni , (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
The purpose of this research is to improve science learning outcomes by using the method of inquiry. This type of research is classroom action research (PTK) using qualitative and quantitative methods. Research subjects are students of class V SDN 03 Ikur Koto Koto Tangah District of Padang. Based on the research cycle I to cycle II, the average scores on the cognitive aspects of the first cycle of 6.7 and the second cycle increased to 8.2. The average score on the affective aspects of the first cycle of 5.9 and the second cycle increased to 8.2. While the average score of 6.1 psychomotor aspects first cycle and the second cycle increased to 8.6. Thus, it can be concluded that by using the inquiry method can improve learning outcomes IPA